2019
DOI: 10.3390/mi10050304
|View full text |Cite
|
Sign up to set email alerts
|

Quantification and Imaging of Antigens on Cell Surface with Lipid-Encapsulated Fluorescent Nanodiamonds

Abstract: Quantifying the density and locating the position of antigens on cell surface has been a challenge in molecular biology research. The challenge lies in the need for a chemically and photophysically stable fluorophore to achieve the required sensitivity and accuracy. Here, we present a method suitable for the purpose by using lipid-encapsulated fluorescent nanodiamonds (FNDs) of 35 nm in diameter as biolabels. The encapsulation of FNDs in biotinylated phospholipids not only facilitates good dispersion of the pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 29 publications
1
4
0
Order By: Relevance
“…Heish et al (2019) demonstrated a system for determining the position and density of antigens on human cells using modulated FND detection. The results aligned with an assay of R-phycoerythrin-conjugated antibodies by flow cytometry, supporting the reliability of this approach ( 87 ). Similarly, FNDs have been shown viable for rapid detection of allergens in foods using a ND-based voltammetric immunosensing platform ( 91 ).…”
Section: Diagnostic Applicationssupporting
confidence: 65%
See 1 more Smart Citation
“…Heish et al (2019) demonstrated a system for determining the position and density of antigens on human cells using modulated FND detection. The results aligned with an assay of R-phycoerythrin-conjugated antibodies by flow cytometry, supporting the reliability of this approach ( 87 ). Similarly, FNDs have been shown viable for rapid detection of allergens in foods using a ND-based voltammetric immunosensing platform ( 91 ).…”
Section: Diagnostic Applicationssupporting
confidence: 65%
“…Rapid detection of viral exposure and infection represents a promising application for FNDs ( 87 , 88 ).…”
Section: Diagnostic Applicationsmentioning
confidence: 99%
“…The problem was simplified by considering the antibody binding region as the flat, bottom surface of the channel (neglecting the height of cells, and diffusion through the cytoplasm) (28)(29)(30)(31)(32) . Approximations were made for the density of antigens on the surface based on antibody binding capacity reported for cell surface antigens in the context of flow cytometry (33)(34)(35). We chose a value of 1×10 5 sites/cell.…”
Section: Methodsmentioning
confidence: 99%
“…19–23 Approximations were made for the density of antigens on the surface based on antibody binding capacity reported for cell surface antigens in the context of flow cytometry. 24–26 We chose a value of 1 × 10 5 sites per cell. Antibody association and dissociation rates ( k on and k off ) were approximated as 1 × 10 5 s −1 m −1 and 1 × 10 –5 s −1 respectively.…”
Section: Methodsmentioning
confidence: 99%